The League of Nations and the Protection of the Environment / Omer Aloni. - Aloni, Omer, 1982- (Cambridge studies in international and comparative law ;, 2021)
In the history of how the law has dealt with environmental issues over the last century or so, the 1920s and 30s and the key role of the League of Nations in particular remain underexplored by scholars. By delving into the League's archives, Omer Aloni uncovers the story of how the interwar world expressed similar concerns to those of our own time in relation to nature, environmental challenges and human development, and reveals a missing link in understanding the roots of our ecological crisis. Charting the environmental regime of the League, he sheds new light on its role as a centre of surprising environmental dilemmas, initiatives, and solutions. Through a number of fascinating case studies, the hidden interests, perceptions, motivations, hopes, agendas and concerns of the League are revealed for the first time. Combining legal thought, historical archival research and environmental studies, a fascinating period in legal-environmental history is brought to life.